2021
DOI: 10.5194/essd-13-1441-2021
|View full text |Cite
|
Sign up to set email alerts
|

Database of petrophysical properties of the Mid-German Crystalline Rise

Abstract: Abstract. Petrophysical properties are a key element for reservoir characterization but also for interpreting the results of various geophysical exploration methods or geophysical well logs. Furthermore, petrophysical properties are commonly used to populate numerical models and are often critically governing the model results. Despite the common need for detailed petrophysical properties, data are still very scarce and often not available for the area of interest. Furthermore, both the online research for pub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Base measurements were taken three times per day at a fixed station to record the instrument drift. A complete Bouguer anomaly was calculated for all gravity measurements by applying the standard correction density of 2.67 kg m -³, which corresponds approximately to the mean rock density of the Tromm Granite (Weinert et al 2021), as also confirmed by the Nettleton method. Particular focus was on the topographic correction, which along some profiles reaches up to 2 mGal due to the steep terrain.…”
Section: Gravity Data/surveymentioning
confidence: 67%
See 2 more Smart Citations
“…Base measurements were taken three times per day at a fixed station to record the instrument drift. A complete Bouguer anomaly was calculated for all gravity measurements by applying the standard correction density of 2.67 kg m -³, which corresponds approximately to the mean rock density of the Tromm Granite (Weinert et al 2021), as also confirmed by the Nettleton method. Particular focus was on the topographic correction, which along some profiles reaches up to 2 mGal due to the steep terrain.…”
Section: Gravity Data/surveymentioning
confidence: 67%
“…The continuous model was converted into a discrete cuboid voxel model with a cell size of 50 x 50 x 50 m. Further decreasing the cell size potentially resolves more details but exponentially increases the computational time of the inversion. As starting value for the rock density, a mean density of the Tromm Granite of 2.67 ± 0.05 g m -³ was defined (Weinert et al, 2021).…”
Section: Inversion Of the Gravity Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This hints at a chemical overprint of the gabbroic diorite by the overlying basaltic andesite, whereas the Ca in the lower part appears to be primary. The spike in τ Ca at a depth of 23.5 m can also be explained by porosity data (Weinert et al, 2021), which can be considered as a measure of fracture density and grain disaggregation in igneous rocks. The porosity decreases sharply from 24 % at a depth of 21.5 m to 3 % at 23.6 m (Fig.…”
Section: Quantification Of Element Transfermentioning
confidence: 99%
“…360 and 320 Ma during the Carboniferous (Powell and Conaghan, 1973;Schulmann et al, 2014). Due to a southward-directed subduction of the oceanic lithosphere below the Armorica microplate, the socalled Mid-German Crystalline Zone (MGCZ) was formed as a magmatic arc at the northern margin of Armorica during the Early Carboniferous; as a highland, this region continuously weathered and eroded until thermal subsidence began to dominate in central Europe (von Seckendorff et al, 2004a;Willner et al, 1991;Zeh and Brätz, 2004;Zeh and Gerdes, 2010). As a consequence, the post-Variscan nonconformity was formed, which represents a diachronous time gap of multiple tens to hundreds of millions years in central Europe (Henk, 1995;Kroner et al, 2007;von Seckendorff et al, 2004b;Zeh and Brätz, 2004).…”
Section: Geological Settingmentioning
confidence: 99%